2014
DOI: 10.1093/mnras/stu1762
|View full text |Cite
|
Sign up to set email alerts
|

Stellar orbits in cosmological galaxy simulations: the connection to formation history and line-of-sight kinematics

Abstract: We analyze orbits of stars and dark matter out to three effective radii for 42 galaxies formed in cosmological zoom simulations. Box orbits always dominate at the centers and z-tubes become important at larger radii. We connect the orbital structure to the formation histories and specific features (e.g. disk, counter-rotating core, minor axis rotation) in two-dimensional kinematic maps. Globally, fast rotating galaxies with significant recent in situ star formation are dominated by z-tubes. Slow rotators with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 80 publications
5
67
0
Order By: Relevance
“…The anti-correlation between V/σ and h 3 is one of the crucial differences between galaxies with and without discs (Bender et al 1994;Krajnović et al 2011Krajnović et al , 2013avan de Sande et al 2017). These anti-correlations are typically found in remnants of gas-rich mergers (Bendo & Barnes 2000;Jesseit et al 2005;González-García et al 2006;Naab et al 2006aNaab et al , 2007Jesseit et al 2007;Hoffman et al 2009;Röttgers et al 2014) or in simulations of objects that did not have a strong feedback mechanism turned on (e.g. no AGN feedback Dubois et al 2016;Frigo et al 2019).…”
Section: Local Kinematic Parametersmentioning
confidence: 79%
“…The anti-correlation between V/σ and h 3 is one of the crucial differences between galaxies with and without discs (Bender et al 1994;Krajnović et al 2011Krajnović et al , 2013avan de Sande et al 2017). These anti-correlations are typically found in remnants of gas-rich mergers (Bendo & Barnes 2000;Jesseit et al 2005;González-García et al 2006;Naab et al 2006aNaab et al , 2007Jesseit et al 2007;Hoffman et al 2009;Röttgers et al 2014) or in simulations of objects that did not have a strong feedback mechanism turned on (e.g. no AGN feedback Dubois et al 2016;Frigo et al 2019).…”
Section: Local Kinematic Parametersmentioning
confidence: 79%
“…This difference in the kinematic behaviour of fast rotators at large radii is illustrated in Figure 3 of Cappellari (2016), and our observations appear consistent with this general picture. Röttgers et al (2014) have found in their simulations that in-situ and ex-situ formed stars follow similar orbit distributions; as such, it is difficult to rule out late dry accretion from the kinematics alone. However, we note that the λR profiles for our FRs are very similar in shape to those presented in Naab et al (2014), which are based on the same simulations as Röttgers et al (2014), for galaxies that have experienced late (z < 2) gas-rich mergers and/or gradual dissipation.…”
Section: Discussionmentioning
confidence: 97%
“…GAMA is a large campaign that combines large multi-wavelength photometric data with a spectroscopic survey of ∼300,000 galaxies carried out using the AAOmega multi-object spectrograph on the AAT. Furthermore, targets were selected from eight highdensity cluster regions sampled within radius R 200 with the same stellar mass limit as for the GAMA fields (Owers et al 2017;Bryant et al 2015). The aim of the SAMI Galaxy Survey selection is to cover a broad range in galaxy stellar mass ( * = M 10 10 8 1 2…”
Section: Sami Galaxy Surveymentioning
confidence: 99%
“…For the cluster environment, we use photometry from the SDSS (York et al 2000) and VLT Survey Telescope ATLAS imaging data (Owers et al 2017;Shanks et al 2013). Stellar masses are derived from the rest-frame i-band absolute magnitude and g−i color by using the color-mass relation following the method of Taylor et al (2011).…”
Section: Ancillary Datamentioning
confidence: 99%
See 1 more Smart Citation